Chronic periodontitis and the risk of head and neck squamous cell carcinoma: facts and figures - Gondivkar, S.M.; Gondivkar, R.S.; Gadbail, A.R.; Chole R.; Mankar M.; Yuwanati M. (Experimental Oncology, 2013)
Substantial evidence supports an association between periodontal disease and several systemic diseases including cardiovascular diseases, diabetes mellitus, respiratory diseases, adverse pregnancy outcomes, osteoporosis etc. Periodontal disease, a chronic inflammatory condition, is highly prevalent in adult populations around the world, and may be preventable. Estimates of prevalence vary between races and geographic regions, with a marked increase in the occurrence of periodontal disease with advancing age. Worldwide estimates for the prevalence of severe periodontal disease generally range from 10 to 15 %. The relationship between periodontal disease and cancer has been examined for a number of specific cancer sites. The grim statistics of head and neck cancer incidence and survival have remained essentially unchanged over the past 3 decades despite the prevention efforts against known risk factors of head and neck cancer, and advances in the diagnosis and treatment, arguing forcibly for new insights regarding the etiology as well as the strategies for prevention. Recent reports have linked periodontal disease with increased risk of squamous cell carcinoma of head and neck. This review provides current literature for a role of periodontal disease in carcinogenesis of head and neck region and discusses possible biological mechanisms involved. Key Words: periodontal disease, head and neck cancer, risk factors